A broadban-tunable photonic bandgap and thermally convertible laser with an ultra-low lasing threshold from a refilled chiral polymer template. Issue 16 (1st April 2019) - Lin, Jia-De; Lin, Hsin-Yu; Wei, Guan-Jhong; Chuang, Yu-Chou; Chen, Lin-Jer; Mo, Ting-Shan; Lee, Chia-Rong
Abstract : This study reports broadband-tunable photonic bandgap and thermally-convertible lasers with ultra-low lasing thresholds based on refilled chiral polymer templates. Abstract : This study demonstrates a broadband-tunable photonic bandgap (PBG) and thermally convertible laser with an ultra-low lasing threshold based on a gradient-pitched cholesteric liquid crystal (CLC) polymer template. The lowest energy threshold of the laser is 16 nJ per pulse under a pumped diameter of ca. 250 μm ( i.e., 0.33 μJ per pulse per mm 2 ), a value that is superior to those of other band-edge lasers based on most dye/quantum-dot-doped CLC systems. Owing to its multiple advantages, such as high stability, ultra-low lasing threshold, wide-band and linear spatial PBG-tunability, and lasing-mode convertibility, the CLC template device can be potentially used for photonics and display applications.